Analysis of IPDN Library Unit Promotional Media Using the AIDA Method - Giwangkara, Dwita; Sardi, Auliya Noviyani (Indonesian Journal of Librarianship, 2024)
Background/Problem Statement: The implementation of information services promotion at the IPDN Library Unit has been studied twice, with the result that these activities were in the category of less good and several forms of promotion had not been implemented effectively. The AIDA method can be applied to break down a promotional activity so that an audience can decide to use a service or product. Most of the previous research has discussed promotional activities with commercial products, whereas non-profit organizations also have products whose existence needs to be known to be utilized. Purpose: This research aims to analyze promotional activities at the IPDN Library Unit using the AIDA method. Method: This research uses a descriptive method with a quantitative approach to describe the activities that are the object of research. Data sources were collected from questionnaires, structured interviews, and IPDN Library database report documents. Result: Library users pay more attention to websites and Instagram as library promotional media. Interest in promotional media in the Library is in short video content and events held onsite. Dissemination activities can double the desire to find out more about information services via Instagram @perpustakanipdn. Increased desire motivates action to access information services at the IPDN Library Unit. Conclusion: Based on the discussion, it can be concluded that the details of the AIDA method can be used by non-profit institutions such as the IPDN Library Unit to increase its existence of information services. Hybrid promotional activities can strengthen promotions by increasing the existence of information services as a library product.